2010
DOI: 10.1002/mnfr.200900343
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of dietary fatty acids on cholecystokinin expression, storage and secretion in enteroendocrine STC‐1 cells

Abstract: Cholecystokinin (CCK) is a peptide hormone secreted from the I-cells of the intestine and it has important physiological actions related to appetite regulation and satiety. In this study we used STC-1 cells to investigate the effects of common dietary-derived fatty acids (FAs) on I-cell secretory function and metabolism. We extend earlier studies by measuring the acute and chronic effects of 11 FAs on CCK secretion, cellular CCK content, CCK mRNA levels, cellular DNA synthesis, cellular viability and cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 55 publications
(67 reference statements)
3
28
0
1
Order By: Relevance
“…In order to assess the impact of samples on CCK secretion in vitro, STC-1 cell line was employed (Pasman et al, 2008, Hand et al, 2010.…”
Section: Cholecystokinin Experiments On Stc-1 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess the impact of samples on CCK secretion in vitro, STC-1 cell line was employed (Pasman et al, 2008, Hand et al, 2010.…”
Section: Cholecystokinin Experiments On Stc-1 Cellsmentioning
confidence: 99%
“…The CCK assay was adapted from Hand et al (2010). Briefly, STC-1 cells were seeded into 12-well plates at a cell density of 2 × 10 6 cells/well, in complete media and incubated overnight.…”
Section: Cholecystokinin Experiments On Stc-1 Cellsmentioning
confidence: 99%
“…Monosaccharides (Mangel et al 1994 ), fatty acids (Hand et al 2010 ), aromatic amino acids (Cordier-Bussat 1998;Wang et al 2011 ), peptidomimetic compounds (Geraedts et al 2011 ) and bitter tastants (Miyata et al 2014 ) have all been demonstrated to dose dependently elicit CCK and GLP-1 secretion from STC-1 cells. Several studies have also reported that sucralose and other sweeteners increase CCK and GLP-1 secretion in STC-1 cells (Geraedts et al 2012 ).…”
Section: Features and Mechanismsmentioning
confidence: 99%
“…For qRT-PCR, standard methods apply. Result interpretation is important as increases in mRNA levels and intracellular peptide levels may not result in corresponding increases in secretion levels of gut peptides (Hand et al 2010 ). A number of sensitive and accurate commercial immunoassays (ELISA and RIA) are available for the detection of CCK, PYY and GLP-1, although multiplexing these analytes has proved diffi cult.…”
Section: Experimental Read Outmentioning
confidence: 99%
“…Cholecystokinin (CCK), a neuropeptide, is secreted in response to intraluminal nutrients by enteroendocrine I-cells of the intestine and has important physiological actions related to appetite regulation and satiety [1]. Postprandial release of CCK is key in activation of intestinal feedback control of gastrointestinal function, comprising short-term inhibition of gastric emptying and acid secretion, stimulation of the exocrine pancreas and gallbladder, and inhibition of food intake [2].…”
Section: Introduction 4)mentioning
confidence: 99%